Developing Tourism, Organising Reports: The Role Of Accounting In Strengthening The Bukik Sangkiang Tourism Working Group - Winingrum, Gusti; Yunita, Ayu Rima; Aprilianti, Dewi; Seprita, Germa; Sari, Gina Marliana; Wahyuni, Lastri; Syarif, Lathifah; Amiratanti, Resi; Delfia, Risna; Amelia, Urmila; Yenti, Winda Sri; Zuhra, Syarifah; Maresti, Dwila; Wafiq, Muhammad (Bhinneka Publishing, 2025)
The development of tourism villages requires synergy between destination potential, institutional capacity building, and transparent financial management. Pokdarwis Bukik Sangkiang, as the main driver of local tourism in Nagari Kumanis, Sijunjung Regency, faces challenges in optimising its tourism potential while also organising its financial reports to be accountable and sustainable. This study aims to analyse the role of accounting in supporting the human resource capacity building strategy of Pokdarwis Bukik Sangkiang, financial recording and reporting mechanisms, and tourism destination branding strategies in Nagari Kumanis. The results show that improving the human resource capacity of Pokdarwis Bukik Sangkiang through management and basic accounting training can strengthen tourism business management skills. The implementation of simple accounting-based financial recording, reporting, and accountability mechanisms increases transparency and the trust of the community and government. On the other hand, the branding strategy of Pokdarwis Bukik Sangkiang through digital promotion and tourism identity based on local wisdom has proven to be effective in increasing the attractiveness of the destination. Thus, accounting not only functions as a recording tool but also as an instrument for strengthening the institutional capacity of Pokdarwis in developing tourism, organising reports, and achieving sustainable destination management.